(untitled) (Global Journal of Management and Business Research, 2024)
In the Kingdom of Saudi Arabia the healthcare sector has been evolving rapidly presenting a dynamic landscape where the pursuit of financial viability intersects with the imperative of social responsibility This study investigates the intricate relationship between profitability and social responsibility and their collective impact on achieving institutional excellence in government and private hospitals Employing an exploratory approach a comprehensive analysis of qualitative and quantitative data was conducted to discern the patterns and trends shaping the healthcare landscape in the context of the Saudi Arabian society The study reveals that while financial viability remains a crucial aspect for the sustenance and growth of hospitals social responsibility has emerged as a key determinant in building trust and establishing long-term credibility within the community Through a review of existing literature combined with in-depth interviews and surveys with healthcare professionals administrators and patients this research underscores the delicate balance required for hospitals to navigate the complex terrain of societal expectations while maintaining financial stability